The Influence Of Students’ Vocabulary Mastery By Utilizing Flashcards For Young Learners In Sixth Grade Of SDN 1 Cisangu - Umay Umay; Yudi Juniardi; Rahman Hakim (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The objective of this study is to assess the influence of utilizing flashcards on vocabulary mastery among sixth-grade students at SDN 1 CISANGU. The research methodology employed was a pre-experimental design involving a one-group pretest-posttest approach. The sample size consisted of one class comprising a total of 26 students. The data for this study were derived from the pretest and posttest results, which were conducted in the format of written tests. The data analysis process involved utilizing the t-test formula. The results of this study for the t-test obtained t arithmetic t table or 5,956 >1,708 then H0 is rejected and H1 is accepted. Thus, it can be concluded that there is an influence of flashcard media on the vocabulary mastery of sixth-grade students of SD Negeri 1 Cisangu. The N-gain test with a result of 0.68 is in the medium category, which means that the utilization of the use of flashcard media is influenced by vocabulary mastery.